PENINGKATAN PENALARAN MATEMATIKA SISWA PADA MATERI KUBUS DAN BALOK DI KELAS V SDN REUKIH KABUPATEN ACEH BESAR - Nisa, Khairun; Anwar, Faisal; Suryawati, Indah (Jurnal Seramoe Education, 2024)
This research is based on the problem of low student learning outcomes and the difficulty students still have in understanding mathematics. This research aims to determine the improvement of students' mathematical reasoning on cube and block material in class V of SDN Reukih, Aceh Besar Regency. This research uses a quantitative approach with a pre-experimental type of research. The sample in this study was 15 class V students consisting of 9 boys and 6 girls. Data collection techniques use tests (pretest and posttest). Data processing techniques are carried out by calculating the average value (x), calculating the standard deviation (S), normality testing and hypothesis testing. The results of the research show that the mathematical reasoning of students in class V of Reukih State Elementary School, Aceh Besar Regency is classified as very good, this can be seen from the average pretest score of 73.13, with a classical learning completeness level of 40%. Meanwhile, the posttest score obtained an average value of 82.80, with a classical learning completion level reaching 93.33%. Based on the results of the hypothesis test, it shows that the calculated t value > t table (12.89333 > 2.14479). So it can be concluded that there is an increase in students' mathematical reasoning on cube and block material in class V of Reukih State Elementary School, Aceh Besar Regency.